Diagnostic Value of Urine sTREM-1 and Urine C-reactive Protein for Infants with Late Onset Neonatal Sepsis - Ozdemir, Senem Alkan; Colak, Ruya; Ergon, Ezgi Yangin; Calkavur, Sebnem (Journal of Pediatric Infectious Diseases, 2020)
Objective Noninvasive markers have been increasingly used as a diagnostic marker for sepsis detection and monitoring of the disease. The aim of this observational, prospective pilot study was to investigate the diagnostic performance of urinary soluble triggering receptor expressed on myeloid cells (sTREM-1) and urine C-reactive protein (CRP) levels in the late onset neonatal sepsis and to compare them with serum CRP levels.Materials and Methods Sixty-six infants with clinical sepsis were included. Urine sTREM-1 and urine CRP were collected at the diagnosis of late-onset sepsis. All laboratory investigations were also noted from the infants.Results There were no significant differences between characteristics of the infants. Culture-positive neonates had significantly higher urine sTREM-1 than culture-negative neonates (p < 0.001). Using a cut-off point for urine sTREM-1 of 129 pg/mL, the sensitivity was 0.63, the specificity was 0.84, positive predictive value was 0.80, negative predictive value was 0.70. Urine sTREM-1 and urine CRP were recollected on the seventh day of sepsis treatment and it was found that the levels of sTREM-1 and CRP decreased.Conclusion This is the first study in the literature which evaluates the place of urine sTREM-1 and urine CRP in the diagnosis of neonatal sepsis. Urine sTREM-1 and urine CRP may be useful in the diagnosis of sepsis and in evaluating the effect of antibiotic treatment.
Keywords: C-reactive protein; late onset neonatal sepsis; neonate; urine sTREM-1